Knowledge of Antimicrobial Drugs among Outpatients in a Specialist Hospital in Abuja, Federal Capital Territory, Nigeria. - Idoko, Lucy O.; Okafor, Kingsley C; Lolo, Nomsu S. (European Journal of Applied Sciences, 2023)
Background: Globally antimicrobials are a key tool in our fight against infectious diseases. Antimicrobial knowledge entails being familiar with the many classes of antimicrobials available and the infections they can treat. Assessing the knowledge of Antimicrobial is necessary among patients to avoid its misuse and development of antimicrobial resistance. It will aid in decision making and improving health seeking behaviour of patients. This study seeks to assess the knowledge of antimicrobial drugs among patients in a specialist hospital in Abuja Muncipal Area council, FCT, Abuja. Methods: This was descriptive, cross-sectional study done in September, 2022 among clients attending outpatient clinic at a District Hospital Abuja's. it involved a sample size of sample size 423 with 400 responding . A multistage sampling technique was adopted for this study. The data was analyzed using the IBM SPSS 28 (Statistical Package for the Social Sciences) computer software (IBM SPSS Inc. 2021). The data was summarized using descriptive statistics which include the percentages, frequencies. Test of association was done using , the chi-square test (χ 2), and p-value less than 0.05 was considered statistically significant. Ethical approval was granted by Bingham University Teaching Hospital, Jos, Plateau State Results: One hundred and fifty respondents (37.5%) had good knowledge of antimicrobials, 141 (35.25%) had fair knowledge of antimicrobials, and 109 (27.25%) had poor knowledge (gave unsatisfactory answers to questions regarding knowledge about antimicrobials). Between male and female respondents. 22% of female respondents had good knowledge, 18.25% had fair knowledge and 16.75% had poor knowledge. Of all the male respondents, 15.5% had good knowledge, 17% had fair knowledge and 10.5% had poor knowledge. There was a statistically significant association between knowledge of antimicrobials with Marital Status (χ² (2, N=400) = 54.92, p < 0.001)where more singles had poor knowledge of antimicrobial than married people, Education (χ² (2, N=400) = 87.16, p < 0.001), where more of those with tertiary education had good knowledge of antimicrobials than those with no education or only primary education. and Age (χ² (2, N=400) = 56.84, p < 0.001) as more younger people (18 - 29 years ) had good knowledge of antimicrobials than older people (40- 59 years).Conclusion: Over a third of clients had good knowledge of antimicrobials, a third also had fair knowledge while about a quarter had poor knowledge. The government and health care workers should support efforts towards improving the knowledge of communities on the basics of antimicrobials, in order to guide its use and improve antimicrobial stewardship.